REALITA PEKERJA ANAK DI WILAYAH PESISIR KOTA TANJUNGBALAI (THE REALITY OF CHILD WORKERS IN THE COASTAL AREA OF TANJUNGBALAI CITY) - Dumora Jenny Margaretha Siagian (Inovasi, 2017)
The number of children working in North Sumatra is one of the social phenomena that shows the family conditions, including children, can not be said to be prosperous. The practice of Child workers are not only take place on land but also in coastal areas, even in the oceans. This study aims to describe the reality of child workers, like the cause of child work, issues of child worker, and protection provided. This research is a qualitative research conducted in Tanjungbalai City. Primary data are come from interview and observation result, and secondary data are come from documentation study and previous research result, that analyzed by qualitative descriptively. The conclusion of the research that there are 3 groups of child workers in Tanjungbalai are drop out of school and forced to work, drop out of school for lazy to study and want to work, and child work but still go to school. Many things cause children to engage in work, where the main factor is the problem of poverty in the family. There are also social and cultural factors that develop in the environment of children, as well as lifestyle that has become the needs of children today. The reality of child worker is very diverse, starting from the abandonment of children's education; Lack of awareness of the employer to education and child health; Non-fulfillment of the right of the child in the form of wages and proper allowances; Unsuitable workplace conditions for children; As well as the unattended child's normal growth. It can be seen that the protection provided to child labor has not been maximized. The recommendation given is the need to socialize the labor laws to companies and parents of child worker optimally and intensely; And supervision and handling of child worker cases. It should also be considered to formulate a local regulation of protection and a special agency that deals with child worker, especially for those working in the informal sector. Keywords: reality, child worker, coastal area, city of Tanjungbalai